TAIWAN’S APPROACH TO WEALTH REDISTRIBUTION: A COMPARATIVE POLITICAL ECONOMY STUDY - Li, Ming-Hsien; Chen, Yu-Chih (International Journal of Allied Research in Economics (IJARE), 2023)
This paper examines the puzzle of why blue-collar workers in many democracies tend to support right-wing parties despite these parties wanting to limit income redistribution. The paper reviews the literature on the heterogeneous effects of democracy on tax and inequality, and argues that the preferences of blue-collar workers are shaped by a number of factors, including their economic insecurity, their cultural values, and their perceptions of the welfare state. The paper concludes by discussing the implications of these findings for the future of democracy and inequality